2016
DOI: 10.1016/j.enconman.2016.02.083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water-containing acetone–butanol–ethanol gasoline blends on combustion, performance, and emissions characteristics of a spark-ignition engine

Abstract: Bio-butanol has proved to be a promising alternative fuel in recent years; it is typically produced from ABE (acetone-butanol-ethanol) fermentation from non-edible biomass feedstock. The high costs for dehydration and recovery from dilute fermentation broth have so far prohibited bio-butanol's use in internal combustion engines. There is an interesting in studying the intermediate fermentation product, i.e. water-containing ABE as a potential fuel. However, most previous studies covered the use of water-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 57 publications
1
26
0
2
Order By: Relevance
“…In addition, the lower particle concentration obtained with hydrous ethanol and anhydrous ethanol blends in comparison to gasoline due to the higher hydrogen to carbon ratio, higher volatility, higher percentage of oxygen content in the fuel, and no sulfur and aromatics in ethanol also favored the repression of PM formation inside the cylinder [69]. Another mechanism for the remarked decrease is the oxidation of PM emission by OH radicals from ethanol [70], and by H, O, and OH radicals from water dissociation [13,71,72]. According to chemical kinetics model results published by Zhang et al [59], the addition of water in fuel encourages the formation of free radicals O, H, and OH, which encourages the oxidation of emissions.…”
Section: Pm Emission Characteristicsmentioning
confidence: 99%
“…In addition, the lower particle concentration obtained with hydrous ethanol and anhydrous ethanol blends in comparison to gasoline due to the higher hydrogen to carbon ratio, higher volatility, higher percentage of oxygen content in the fuel, and no sulfur and aromatics in ethanol also favored the repression of PM formation inside the cylinder [69]. Another mechanism for the remarked decrease is the oxidation of PM emission by OH radicals from ethanol [70], and by H, O, and OH radicals from water dissociation [13,71,72]. According to chemical kinetics model results published by Zhang et al [59], the addition of water in fuel encourages the formation of free radicals O, H, and OH, which encourages the oxidation of emissions.…”
Section: Pm Emission Characteristicsmentioning
confidence: 99%
“…e combustion duration of ABE-diesel blends is shorter, and the natural flame luminosity is lower in comparison with diesel, which indicated ABE-diesel blends had potential advantages of improving energy efficiency and reducing soot emission in engine. His group also tested the impacts of factors such as blend ratio, mixture formulation, and water addition on ABE-gasoline blends performance and emissions [25][26][27]. A phenomenological soot model considering the oxidation effect on soot density was proposed for ABE by Zhao et al [28].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Sendzikiene et al [13] optimised rapeseed biodiesel production by Response Surface Methodology (RSM) for enzyme catalysed transesterification and achieved maximum biodiesel yield of 96.6%. In addition of this, there have been number of studies found in literature upon growing concern towards development of renewable energy resources [14][15][16] and for abatement of exhaust emissions of diesel engine with use of biofuels [17][18][19][20][21][22]. Upon reviewing the above literature, it can be said there has been some work reported for use of bio-based short chain alcohols but no study work on optimisation of transesterification process variables having comparative analysis of impact of different alcohols on biodiesel yield and quality.…”
Section: Introductionmentioning
confidence: 99%